THE INFLUENCE OF HUMAN RESOURCE POLICIES ON EMPLOYEE SATISFACTION AND RETENTION - Mochamad Heru Riza; Dewi Qomariah Imelda, Tati Hariyati (Adiba Aisha Amira, 2024)
This increasingly fierce digital era business competition forces companies to more carefully manage quality human resources. This research uses a literature study to analyze the importance of human capital policies in improving employee satisfaction and retention. The findings show that effective human capital policy formulation and implementation play a vital role in retaining competent employees. The practical implications of this study include suggestions for organizations to re-evaluate and refine employee management policies with a focus on aspects that have been shown to influence employee loyalty and attraction. The research also emphasizes the importance of comprehensive human resource management to create a supportive and motivating work atmosphere for people.